Mechanical performance of lap joints of flat roof waterproofing membranes subjected to artificial weathering - Gonçalves, M. (2020)
The flat roof of a building, here understood as the whole of every construction element from the ceiling to the surface exposed to climatic agents, is made of a set of horizontal or quasi-horizontal layers that satisfy its functional demands. The waterproofing layer is fundamental in most flat roofs and, of the various options, single-layer systems made of prefabricated membranes and mechanically fastened are one of the most frequently used in Portugal. This solution is also used to repair roofs’ waterproofing systems without having to remove the existing layers, thus reducing the cost. However, it is well known that the performance of these systems is strongly influenced by the efficiency of the membrane fastenings, which is directly related to the membranes’ nature and the design and execution of the lap joints. Many of the anomalies that occur are related to the deficient execution of the membranes’ lap joints1–3 and the consequent faulty performance when subjected to average environmental agents. Studies undertaken in Portugal on the behavior of lap joints in membranes made or commercialized in this country4,5 have corroborated other studies in this area and shown that certain membranes perform worse than others when used in single-layer systems. Three different solutions were tested: amyloid precursor protein (APP)- and Styrene-Butadiene-Styrene (SBS)-modified bituminous membranes and polyvinyl chloride (PVC) membranes. Of the bituminous membranes, the SBS ones produced and commercialized in Portugal presented, as expected, much more satisfactory mechanical characteristics than the APP ones, thus justifying a more thorough study of their suitability for use in mechanically fastened single-layer systems.